Molecular docking of viral protein 1 of Bursal infectious disease virus and phytoconstituents of Withania somnifera (L.) Dunal: A computational approach - Gayozo, Elvio (2022)
Infectious bursal disease is a pathology of viral origin that affects poultry, causing a high mortality rate. Existing vaccines face the problem of the appearance of new strains, so searches are made for molecules with potential binding affinity to viral proteins. Withania somnifera extract is involved in the replication of infectious bursitis virus, but the possible mechanism of action is not well understood. The aim of this study was to identify, through in silico methods, the phytoconstituents of W. somnifera with binding affinity to the active site of viral protein 1 (VP1) of infectious bursal disease virus. Molecular docking assays were performed between VP1 and 27 phytoconstituents described in W. somnifera. The binding energy data obtained were analysed with the Kruskal-Wallis test and Dunn’s test (p<0.05). The results showed that the compounds somniferin, withanolide A, withanolide N, withanolide R, withanolide S and witasomniferol C presented significantly favourable binding free energy (p<0.001) with values of -8.92±0.15, -7.98±0.20, -7.56±0.28, -8.09±0.01, -8.39±0.01 and -7.99±0.23 kcal.mol-1, respectively. The residues identified in the interactions between VP1 and the phytoconstituents were Arg175, Arg335, Asp402, Asn403, Lys419, Glu421 and Asn493, which possess crucial functions in the viral genome replication process. The phytoconstituent with the best docking result to VP1 was somniferin, which showed favourable binding affinities to the active site of the protein; however, in vitro experimental validation of these observations is required.